Neurovascular communication during CNS development - Paredes Ugarte, Isidora B.; Himmels, Patricia; Ruiz de Almodóvar, Carmen (Developmental cell, 2018)
A precise communication between the nervous and the vascular systems is crucial for proper formation and function of the central nervous system (CNS). Interestingly, this communication does not only occur by neural cells regulating the growth and properties of the vasculature, but new studies show that blood vessels actively control different neurodevelopmental processes. Here, we review the current knowledge on how neurons in particular influence growing blood vessels during CNS development and on how vessels participate in shaping the neural compartment. We also review the identified molecular mechanisms of this bidirectional communication.